Discourse and the construction of society : comparative studies of myth, ritual, and classification - Lincoln, Bruce (Oxford University Press, 1989)
This is a paperback reprint of a book published in 1989. Lincoln explores the ways in which myth, ritual, and classification hold human societies together - and how, in times of crisis, they can be used to take a society apart and reconstruct it.